The relationship between blood lactate and heart rate responses to swim bench exercise and women's competitive water polo - Konstantaki, M.; Trowbridge, E. A.; Swaine, I. L. (Journal of Sports Sciences, 1998)
The aim of this study was to explore the relationship between physiological responses to dry-land testing and to water polo playing. Eight female water polo players (mean ± s: age 26.7 ± 5.7 years, height 169 ± 6 cm, body mass 65.3 ± 7.0 kg) participated in two assessments. The first involved a discontinuous incremental arm test to exhaustion on an isokinetic swim bench. Blood lactate was determined from finger-prick blood samples and heart rate was recorded at increasing exercise intensities. The highest (peak) values for blood lactate (5.1 ± 0.2 mmol 1 −1), exercise intensity (79 ± 5.2 W) and heart rate (146 ± 6 beats min −1) were recorded at exhaustion. Also, the exercise intensity and heart rate at a blood lactate concentration of 4 mmol 1 −1 were established. The second assessment involved determination of blood lactate and heart rate immediately after each quarter of a different water polo game for each subject. The mean (± s x¯) blood lactate and heart rate for each quarter of the game were as follows: 3.5 ± 0.4, 4.3 ± 0.5, 4.3 ± 0.7 and 4.6 ± 0.5 mmol l −1; 138 ± 10, 149 ± 12, 151 ± 9 and 154 ± 8 beats min −1, respectively. None of the peak values on the swim bench correlated with blood lactate or heart rate responses to game-playing. However, the mean exercise intensity at 4 mmol l −1 lactate (64 ± 5 W) correlated with the fourth quarter values of both blood lactate concentration ( r = −0.82, P = 0.01) and heart rate ( r = −0.93, P < 0.001). These results show that submaximal metabolic responses to exercise on a swim bench are closely correlated with metabolic responses to water polo game-playing.